Relasi Komunikatif Verbal Antara Al-Qur’an, Lukman, Dan Anaknya (Kajian Semantik Al Qur’an) - Muh. Hikamudin Suyuti (Hikamatzu | Journal of Multidisciplinary, 2025)
A This study aims to examine the communication relationship among the Qur'an, Luqman and his son. This research is a qualitative research implementing literature research method. The data in this study comes from primary data and secondary data. The primary data is the text of the Qur'an surah Luqman verses 12-17, and the secondary data are books and other written documents. Based on the thoughts expressed by the Qur'an towards Luqman, Luqman knows the terms and ideas elaborated in the Qur'an consisting of religious issues such as tawhid and righteous deeds. Then, Luqman taught those points to his son about faith, being dutiful to both parents, and attitude of responsibility for the action and behavior.